Impact of Non-Interest Income on Financial Performance of Joint Venture Banks in Nepal - Shah, Ajay Kumar; Agarwal, Niraj; Phuyal, Ram Kumar (Journal of Business and Social Sciences Research, 2018)
The research was conducted to identify the non-interest income variables that will likely affect the financial performance of the joint venture banks of Nepal. The main objective of the study is to analyze the prominence of non-interest income and its effect on financial performance of joint venture banks in Nepal. This study will help the banks to identify other sources of income of the bank and try to look at its impact on the overall profitability and risk intention. To measure the financial performance, the indicator of profitability i.e. returns on assets and return on equity are taken into consideration for the study as a dependent variable and assets size, letter of credit fee, guarantee income, remittance fee, dividend income, exchange income, service charge, and renewal fee as an independent variable. Both descriptive and inferential analyses were performed to capture the relationship. From the result analysis, it is observed that the non-interest income variables that would affect the financial performance of the joint venture banks. It is observed that not all variables have equal effect on the profitability as measure of financial performance, for joint ventures the factors like assets size, letter of credit fee, guarantee income, remittance fee, dividend income, exchange income, service charge, and renewal fee have a significant relationship with the measure of financial performance that is return on assets and return on equity. Apart from the interest income, there are lot of non-interest variables which leads to profitability so the banks looking to increase its profitability with lesser risk need to take these variables into consideration. Results indicate that banks need to keep the non-interest income variables into consideration at times for improving the financial performance of the joint venture banks.